1997
DOI: 10.2134/agronj1997.00021962008900060009x
|View full text |Cite
|
Sign up to set email alerts
|

Swine Lagoon Effluent Disposal by Overland Flow: Effects on Forage Production and Uptake of Nitrogen and Phosphorus

Abstract: Swine (Sus scrofa) production requires economical and environmentally safe waste management systems. The objective of this study was to determine the effect of swine lagoon effluent on dry matter yield and N and P uptake of a mixture of hybrid bermudagrass [Cynodon dactylon (L.) Pers. cv. Russell] and annual ryegrass (Lolium multiflorum Lam.) grown on a Marvyn loamy sand (fine‐loamy, kaolinitic, thermic Typic Kanhapludult). Treatments included a control with no nutrient additions, NH4NO3 at 560 kg N ha−1 yr−1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…Nitrogen uptake by rice plants was disproportionately greater in treated plots compared with the low rate plot (C195), at approximately 230% and 300% for the T450 and T600 treatments, respectively. The rate of nitrogen recovery by rice plants (32-67%) in this study was similar to that reported for bermuda grass treated with swine effluent (40-75%; Adeli et al 2003;Whalen and DeBerardinis 2007) but higher than the rate reported by Liu et al (1997) (13-32%) and Carey et al (1997) (20%).…”
Section: Discussionsupporting
confidence: 88%
“…Nitrogen uptake by rice plants was disproportionately greater in treated plots compared with the low rate plot (C195), at approximately 230% and 300% for the T450 and T600 treatments, respectively. The rate of nitrogen recovery by rice plants (32-67%) in this study was similar to that reported for bermuda grass treated with swine effluent (40-75%; Adeli et al 2003;Whalen and DeBerardinis 2007) but higher than the rate reported by Liu et al (1997) (13-32%) and Carey et al (1997) (20%).…”
Section: Discussionsupporting
confidence: 88%
“…Adeli et al (2003) showed an overall recovery of 40% of waste-N following two applications of swine effluent over a growing season, but the maximum recovery of 51% was observed in the fall fertilization. Liu et al (1997) reported dry matter N recoveries of 13-32% over the course of a 2-year study in Alabama.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in crop yield from the contribution of N in livestock manure have been documented by various researchers (Beauchamp 1983;Xie and MacKenzie 1986;Montavalli et al 1989;Jokela 1992;Liu et al 1997;Schoenau et al 1998a). However, crop availability of total N in manure is generally lower than N contained in inorganic fertilizer because of the slow release of organically bound N and the volatilization of NH 3 from surface-applied manure (Klausner and Gust 1981;Beauchamp 1983).…”
mentioning
confidence: 94%